The relevance of physical album for indie band in digital era / Muhammad Hazim Abdul Hamid - Abdul Hamid, Muhammad Hazim (2019)
Indie music started as an underground movement and began to emerge in the mainstream arena. At its peak, indie music almost overcame the popularity of mainstream music. Indie music also enhanced its position as part of Malaysia's mainstream culture during its glory days. Some of indie band and artists not dare to release a full album in physical because the advent of digital music has dominated all physical markets. This research will indentify the relevance of physical album for indie band in digital era. Other than that, this research also discover what indie band fans seek in a physical album and to understand how indie band fans gain product information related to the bands that they follow. This research uses qualitative methods such as conducting research on library materials and using digital tools which is e-journals and e-books. Other than that, field research method which is interview by serve three set of questionnaire on 52 respondents. The respondent was from random of indie band fans in Malaysia. Therefore, this research had concluded that this study had a successfully achieved all the objective stated and had proven gained a lot of attention from indie band fans.